Gregory T. Clark, Art in a Time of War: The Master of Morgan 453 and Manuscript Illumination in Paris during the English Occupation (1419–1435) - Serchuk, Camille (Speculum, 2019)
Keywords: book.review; dept.art

Review of Images, pouvoirs et normes [Review of the book Images, pouvoirs et normes: Exégèse visuelle de la fin du Moyen Âge] - Serchuk, Camille (H-France Review, 2019)
Keywords: book.review; dept.art; ⛔ No DOI found

Quand les artistes dessinaient les cartes: vues et figures de l'espace français, Moyen âge et Renaissance [exposition, Paris, Hôtel de Soubise-Musée des Archives nationales, 25 septembre 2019-6 janvier 2020] - Dumasy-Rabineau, Juliette; Gastaldi, Nadine; Serchuk, Camille (le Passage Archives nationales, 2019)
Keywords: SCSU Faculty Scholar Award; award_winner; dept.art

Sabbatical Leave 2018-19 Follow-up Report. - Brownell, Mia (2019)
Two term sabbatical to create "Baroque Float", an extensive number of paintings investigating the visual and conceptual correlation between the structures of life as depicted by scientific molecular/cell imaging and structures of art as depicted by still life and Baroque ceiling painting.
Keywords: dept.art; faculty_collection; sabbatical_report

Around the world: Borders and frames in two sixteenth-century Norman map books - Serchuk, Camille (Maps and Travel in the Middle Ages and the Early Modern Period, 2019)
Keywords: dept.art